Molecular cloning and expression of heterologous genes encoding xylose-utilizing enzymes in the yeast Saccharomyces cerevisiae - Moes, Catharine Jacoba,1971- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1996.